Penyelesaian Kredit Bermasalah Menurut Undang – Undang (UU) No. 10 Tahun 1998 - Arya Rizqy R; Ilham Fauzi (Journal of Cultural Relativism (JCR), 2024)
Banks are financial institutions that have an important role in the economy by providing financial services to the public. Its main function includes collecting funds from the community through various products such as savings and deposits, as well as channeling these funds back in the form of credit or loans to the community. The aim of this research is to find out the credit application procedure involves various stages of inspection and verification to ensure the debtor's suitability. In this writing regarding the resolution of problem (bad) credit using a normative legal approach (legislation), whether the handling of bad credit can be resolved through a mediative model, or must it be resolved through legal process (court). In principle, granting credit starts from submitting an application by the customer (potential debtor) through a credit application letter to the creditor (bank). This application letter functions as proof that the prospective debtor has initiated a transaction for the planned disbursement of loan funds in the form of credit. Next, this process is followed by fulfilling various subjective and objective requirements. If bad credit occurs because the debtor does not carry out its achievements as stated in the credit agreement, then before executing the collateral, the debtor must first be declared in default, which is done through a court decision.